Cervical Sonoelastography and Cervical Length Measurement but not Cervicovaginal Interleukin-6 Are Predictors for Preterm Birth - Weichert, A.; von Schöning, D.; Fischer, T.; Thomas, A. (Ultrasound International Open, 2016)
Worldwide, preterm birth annually affects more than 15 million infants. Despite increasing knowledge of the risk factors and mechanisms associated with preterm labor, the preterm birth rate has risen in most industrialized countries. The ability to identify women at high risk for spontaneous preterm birth is crucial yet remains difficult. The aim of the present study was to assess the value of cervical length measurements in combination with sonoelastography and interleukin 6 (IL-6) concentrations in cervicovaginal secretions to identify women at risk for preterm birth.36 pregnant women with signs of threatened preterm birth were enrolled in our prospective cohort study. Cervical length measurement, sonoelastography, and IL-6 levels from cervicovaginal swab samples were measured.The preterm birth rate was found to be 33.3% in our study cohort. Maternal age did not differ between the preterm and term birth groups. Measurement of the cervical length alone was found to have a sensitivity of 0.7 and a specificity of 0.8, whereas cervical sonoelastography had a sensitivity of 0.66 and a specificity of 0.82. By using a combination of both methods, the sensitivity and specificity were found to be 0.9 and 0.7, respectively. IL-6 levels were not found to differ between women with term deliveries and women with preterm births.Both, cervical sonoelastography and cervical length measurement are valuable tools in identifying women with threatened preterm birth. The highest correlation with the outcome preterm birth was achieved using a combination of both cervical length measurement and cervical sonoelastography.
Keywords: sonoelastography; cervical length; preterm birth; cervix